MENUMBUHKAN MINAT LITERASI ANAK USIA DINI MELALUI ALAT PERMAINAN EDUKATIF (APE) ICE CREAM DI TK NAJIHAH DESA BOTUNG - Harahap, Rani Astria Silvera; Hasibuan, Syamroh Habibah; Pulungan, Lisda Khairani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Literacy is a person's ability to understand information processed through reading and writing activities. The results of a study conducted by Alibaca obtained that the National Literacy Index is included in the category of low literacy activity, including the province of North Sumatra with a value of 35,73. To improve the literacy of the community which is still low, the introduction of literacy must be done from an early age in addition to habituation, the introduction of literacy from an early age also provides many benefits, one of which is that children are easier to process, receive and respond to all information he receives. One way to foster an interest in early childhood literacy is to use the Ice Cream Educational Game Tool (APE). This community service is located in Botung village, precisely in Najihah Kindergarten. The purpose of this community service is to foster an interest in early childhood literacy. The method used participatory Rural Appraisal (PRA). The implementation of this service is carried out through four stages, namely: analysis of the situation, program planning, implementation, and evaluation. After this community service activity was carried out, the results were obtained that by using the Educational Game Tool (APE) ice cream the interest in early childhood literacy in Botung village increased.